Functionalization of single-walled carbon nanotubes with (R-)oxycarbonyl nitrenes - Holzinger, Michael; Abraham, Jürgen; Whelan, Paul; Graupner, Ralf; Ley, Lothar; Hennrich, Frank; Kappes, Manfred; Hirsch, Andreas (Journal of the American Chemical Society, 2003)
Sidewall functionalization of single-walled carbon nanotubes (SWCNTs) via the addition of (R-)-oxycarbonyl nitrenes allows for the covalent binding of a variety of different groups such as alkyl chains, aromatic groups, dendrimers, crown ethers, and oligoethylene glycol units. Such additions lead to a considerable increase in the solubility in organic solvents such as 1,1,2,2-tetrachloroethane (TCE), dimethyl sulfoxide (DMSO), and 1,2-dichlorobenzene (ODCB). The highest solubilities of 1.2 mg/mL were found for SWCNT adducts with nitrenes containing crown ether of oligoethylene glycol moieties in DMSO and TCE, respectively. The presence of chelating donor groups within the addends allowed for the complexation of Cu and Cd. Atomic force microscopy (AFM) and transmission electron microscopy (TEM) revealed that the functionalized tubes form thin bundles with typical diameters of 10 nm. The presence of thin bundles in solution is supported by H NMR spectroscopy. The elemental composition of the functionalized SWCNT was determined by X-ray photoelectron spectroscopy (XPS). The use of Raman and electron absorption spectroscopy (UV/Vis-nIR) showed that the electronic properties of the SWCNTs are mostly retained after functionalization, indicating a low degree of addition within this series of SWCNT derivatives.